SOME PROBLEMS OF THE STOCK MARKET OF COMMERCIAL BANKS AND WAYS TO SOLVE THEM - Sharipova Farida Asadovna (Journals Park Publishing, 2024)
In this article it is analyzed the factors influencing the activities of commercial banks in the stock market. It is also developed proposals and practical recommendations aimed at solving these problems and increasing the activity of banks in the stock market.
Keywords: banks, stock market, securities, inflation, liquidity, profitability.